PROSES MANUFAKTUR MESIN PEMOTONG KERUPUK IKAN DENGAN KAPASITAS 100KG/JAM - Azmi Athallah (2021)
Fish is one of the foodstuffs that has little interest in Indonesia, which is a country with quite abundant fish catches. Therefore, to encourage people's interest in consuming fish, there are many processed ways so that people can enjoy it deliciously, one of which is by making fish crackers. In this paper, the theme of the manufacturing process is in the manufacture of fish cracker cutting machines. The purpose of this paper is to produce a fish cracker cutting machine with a process that does not consume too much production costs and the selection of the right material and can also save production time. The selection of the right manufacturing process can be used by analyzing the manufacturing process with the parameters of the costs incurred in each formation or purchase of machine parts, the length of processing time, and the selection of materials used in the fish cracker cutting machine to be made.